Parametric Analysis of Control Techniques for 15 MW Semi-Submersible Floating Wind Turbine - Taesu Jeon; Byung-Soo Kim; Jaecheon Kim; Insu Paek; Chang-Hyuck Lim (Applied Sciences)
In this study, a composite control algorithm based on classical control methods is developed to achieve all control objectives, such as power production, load reduction, and motion reduction, for the floating wind turbine. In previous studies, peak shaving and nacelle feedback were used together to reduce both platform motion and the tower-base loads of floating wind turbines. The new approach presented in this study not only addresses the platform motion and tower loads but also aims to mitigate the rotor speed fluctuations and the blade loads by additionally introducing feedforward control and individual pitch control. This expansion enhances the applicability and control performance of classical control algorithms. To achieve this, parametric simulations were conducted using OpenFAST to assess the effects of control parameter variations for each control technique. The simulation results showed that the proposed control algorithm significantly reduced the rotor speed fluctuations, tower loads, blade loads, and platform motion compared with the baseline controller.